1072. SARS-CoV-2 Antibody Levels Associate with Neutrophil Activation. (15th December 2022) - Warner, Seth; Miao, Rui; Ramos-Benitez, Marcos J; Tian, Xin; Reger, Robert; Burbelo, Peter D; Kanthi, Yogendra; Kanthi, Yogendra; Cohen, Jeffrey I; Suffredini, Anthony F; Nathan, Steven D; Childs, Richard W; et al.
Abstract: Background: COVID-19 disease severity and outcomes have been linked to high antibody titers and a dysregulated neutrophil immune response. Here we query associations and connections between the endogenous SARS-CoV-2 antibody response and neutrophil activation in COVID-19. Methods: Baseline serum or plasma samples from 57 patients hospitalized on oxygen with COVID-19 were used to perform; 1) quantitative measurements of SARS-CoV-2 specific antibodies using a luciferase-based immunoprecipitation system assay, 2) quantitative measurements of neutrophil specific biomarkers using Luminex technology, and 3) neutrophil extracellular traps (NETs) as measured by myeloperoxidase-DNA (MPO-DNA) complexes by ELISA. Absolute neutrophil count (ANC) and immature granulocyte count (IGC) were measured from complete blood counts (CBC). Antibody levels were compared by disease severity using Wilcoxon rank-sum test and correlations were generated between antibody levels and neutrophil activation markers using Spearman's correlation (SC). Results: In a cohort of hospitalized patients, severe/critical COVID-19 was associated with higher levels of nucleocapsid-IgA (p=0.011) as well as spike-IgG (p= 0.0007) compared to moderate disease, while spike-IgA and nucleocapsid-IgG showed similar associations, trending towards significance (Figure 1A). Levels of IgG-spike and IgG-nucleocapsid both had significant correlations with the ANC (SC 0.33, p = 0.029; SC 0.38 p = 0.012). All four antibody titers showed strong correlations with IGC, lactoferrin and lipocalin-2, evidence of emergency granulopoiesis. Further, S100A9, a component calprotectin correlated with spike-IgG and nucleocapsid-IgA levels (SC 0.29, p = 0.030, SC 0.29 p = 0.029). Lastly, we found circulating NETs correlated with spike IgA levels (SC 0.38 p = 0.006), and its correlations with IgG-spike and IgA-nucleocapsid additionally approached significance with NETs levels as well (Figure 1B). Antibody Levels Correlate with Disease Severity and Neutrophil Activation Markers Figure 1: A) Levels of anti-Spike and anti-Nucleocapsid IgA and IgG levels measured in the serum of 57 unvaccinated hospitalized COVID-19 patients. Moderate illness represents ordinal scale 5 requiring low flow oxygen, while severe/critical patients represent ordinal scale 6 and 7, requiring high flow oxygen, non-invasive or mechanical ventilation, respectively. P values are compared by a Wilcoxon ranked sum test. B) Heatmap showing Spearman correlations between levels of anti-Spike and anti-Nucleocapsid IgA and IgG and markers of neutrophil activation. P values for individual correlations are represented in parentheses. MPO (myeloperoxidase), ANC (absolute neutrophil count), S100A9 (S100 calcium binding protein A9). Conclusion: Higher anti-spike and anti-nucleocapsid IgG and IgA levels associate with more severe COVID-19 illness. Further, endogenous SARS-CoV-2 specific antibody levels associate with markers of emergency granulopoiesis and neutrophil activation. Inhibiting antibody mediated neutrophil activation may improve outcomes in COVID-19. Disclosures: All Authors : No reported disclosures.